Molecules and models the molecular structures of main group element compounds - Haaland, Arne. (Oxford : Oxford University Press, 2008)
This book describes the structures of molecules, i.e. their shape and size, as determined by experiments or advanced theoretical calculations, and gives an introduction to the simple concepts that chemists use to interpret these structures.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular structure; Molecules -- Models